PENGARUH PENAMBAHAN LIMBAH CAIR PABRIK KELAPA SAWIT DAN EM4 DALAM PROSES PENGOMPOSAN TANDAN KOSONG KELAPA SAWIT PADA PT. LADANGRUMPUN SUBURABADI DI KABUPATEN TANAH BUMBU KALIMANTAN SELATAN - Tjahjo M. Widjajanto; Idiannor Mahyudin; Fakhrur Razie; Ahmadi Ahmadi (EnviroScienteae, 2021)
The objective of the research was to analyzes the exact treatment of Oil Palm EFB composting ussing POME , Bioactivator, and POME with Bioactivator in a given time and to analyze the best buildup of nutrients from Oil Palm EFB composting process with POME and Bioactivator. Then to analyze the best velocity for Oil Palm EFB composting process for POME and Bioaktivator addition. This research was conducted in two month at area of oil palm  plantations in  PT Ladangrumpun Suburabadi district Tanah Bumbu. The research was arranged in Random Design of Factorial Group (RDFG) and consists of one treatment factor with 4 group replications for experiment i.e ;PO ( EFB 75 kg (control)), P1 (EFB 75 kg added POME), P2 (EFB 75 kg added Bioactivator dose 100 cc), P3 (EFB 75 kg added POME and Bioactivator dose 100 cc). As a maturity indicator, the C/N value ratio at 54 days after application has not reached its standart , but the end of incubation period  for 10 months has reached compost maturity with C/N < 20 (setyorini,2012). Phase 1 C/N ratio 50.10 – 74.3 best on control (no treatment) and in stage two months, it has a C/N ratio of 6.47 – 10.13, then the lowest on control. The treatment of EFB with POME and Bioactivator has increased the content of nutrients, at 54 days after aplication for N  at 0.53% control, P at combination of EM4 + POME 0.19% and K at combination of EM4 + POME 0.56%. In 10 months the best N nutrient at EM4 1.21%, P at combination of EM4 + POME 0.14%, and K at combination of EM4+POME 1.21%.